2000
DOI: 10.1021/om0004850
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Stereoelectronic Parameters of PF3, PCl3, PH3, and P(CH2CH2CN)3. The Quantitative Analysis of Ligand Effects (QALE)

Abstract: Using the QALE model, we determined the electronic parameters for PF3 (χd = 44 ± 4, E ar = 0, πp = 14 ± 1), PCl3 (χd = 42 ± 1, E ar = 4.1 ± 0.3, πp = 5.3 ± 0.5), PH3 (χd = 17 ± 1, E ar = 0, πp = 3.7 ± 0.7), and P(CH2CH2CN)3 (χd = 17.0 ± 0.6, E ar = 0, πp = 1.2 ± 0.2). These values indicate that PF3 and PCl3 are comparable in σ donor ability and are the poorest σ donor ligands we have studied. Both PH3 and P(CH2CH2CN)3 are reasonably good σ donors, comparable in strength to P(p-ClC6H4)3. PF3 is by far the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 107 publications
0
51
0
1
Order By: Relevance
“…16) [64], but with a new P-R bond that has the potential to improve precursor stability and thus suitability for EBID. This approach is supported by the successful synthesis of ClAuPF 2 R complexes [65], although no EBID studies with these organometallic precursors have been reported.…”
Section: Strategies For Au Precursorsmentioning
confidence: 99%
“…16) [64], but with a new P-R bond that has the potential to improve precursor stability and thus suitability for EBID. This approach is supported by the successful synthesis of ClAuPF 2 R complexes [65], although no EBID studies with these organometallic precursors have been reported.…”
Section: Strategies For Au Precursorsmentioning
confidence: 99%
“…For example, after protection of the secondary alcohol of 11a as a silyl ether, the ester group of 14 could be smoothly reduced using LiAlH 4 . After 1h at 0°C in Et 2 O, the primary alcohol 15 could be isolated in 84% yield (Scheme 11).…”
Section: Resultsmentioning
confidence: 99%
“…The solution was stirred 3 days at room temperature. Then aqueous NH 4 Cl was added and the aqueous layer was extracted with Et 2 O. The organic layer was washed with brine, dried over MgSO 4 and concentrated.…”
Section: Methodsmentioning
confidence: 99%
“…Choosing relevant descriptors is a challenge. [16,[36][37][38] Descriptors can be determined either from the molecular structure, or the physical properties. [14] Table 1 shows some typical examples of molecular descriptors for the complex shown in Figure 4.…”
Section: Case Study: Ni-catalysed Hydrocyanationmentioning
confidence: 99%